Analysis of the composition of Malay traditional house compound: a case study of Kg Seri Tanjung, Melaka - N Murtaza, Fatin Farhana; Ibrahim, Illyani; Harun, Nor Zalina; Abdullah, Alias (Centre For Sustainable Urban Planning & Real Estate (SUPRE) Faculty of Built Environment, University of Malaya, 2018)
The study of Malay settlement that focus on the individual house compound is important in developing the future city that carries the Malay identity. The original Malay traditional house usually have an open space at outside of their house which is called as house compound and has its own functions. However, as a household increase, the house in a lot is extended and has decrease the sizes of house compound. The modernization also has changed the functions and positions of some elements of the house compound like the hard landscape. Thus, the objectives of this paper are to; 1) analyses the current elements of traditional house compound in Kg Seri Tanjung and 2) prepare a preliminary framework of Malay traditional house compound. The method of this study is by using thematic analysis that results in the formation of the framework of traditional Malay house compound. GIS data analysis is used in mapping the traditional houses in the study area. The percentage of the elements of Malay traditional house compound is analyses by using frequency analysis gathered in SPSS data. The main findings of this study show that the Malay traditional houses in Kg Seri Tanjung are still preserving the design of Malay house compound through the preservation and the position of hard landscape element in their house compound. The framework for Malay traditional house compound in Kg Seri Tanjung shows that the composition of Malay house compound has planting at in front of the house as their decoration or fences to mark the house boundary and the position of suspension, pen, coop, shed and external toilet are at the side or backyard of the house. Thus, this shows that the installation of Malay traditional house features in house compound are still relevant in current development. Further study will focus on the density study of Malay traditional village in Kg Seri Tanjung.